(untitled) (Research, Society and Development, 2023)
Cleft palate is a multifactorial defect that occurs in intrauterine life, because there is no complete fusion of the maxillary processes. Thus, palatoplasty aims to repair the cleft and has techniques that improve the patient’s quality of life. Objective: To evaluate the techniques used in palatoplasty surgery, highlighting the one with the best results in terms of management and postoperative period. Methodology: Integrative literature review study, searching Scielo and Pubmed databases from January to october 2023. The selected articles had a time frame from 2004 to 2021, and of the 545 articles found, 25 were used. Results: The authors reported the prevalence of clefts and their classification. In addition, regarding the techniques, they addressed similar results in postoperative success rates and management, in addition, they came to the conclusion that there are techniques that increase the incidence of fistula and nasalance. Discussion: There was debate among the authors regarding the predilection of cleft palates. There was disagreement regarding the preference for one-stage and two-stage surgery. Furlow’s and Bardach’s techniques showed similar results and showed better success rates. Conclusion: Therefore, it is concluded that the choice of surgical technique regarding management is the choice of the professional. On the other hand, in terms of treatment effectiveness, the Furlow and Bardach techniques proved to be more effective.